NEW YORK. (Strad, 2006)
Reviews several concerts in New York City including a performance by the Mendelssohn Quartet at the Metropolitan Museum of Art on March 10, 2006 and by the Young Danidh Quartet at the Scandanavia House on March 30, 2006. INSET: REVIEWER BIOGRAPHIES.